Detection and molecular characterisation of Group A rotavirus from children in northern Botswana - Kabaabetswe, LP; Sebunya, TK; Matsheka, MI; Ndung'u, T (East African medical journal, 2005)
To determine the presence of group A rotavirus in human stool samples in northern Botswana and to characterise the circulating strains. A cross sectional study. The University of Botswana and Botswana-Havard Partnership for HIV Research. A total of 210 stool samples was collected; 104 from hospitalised and 106 from non-hospitalised children, five years and below suffering from gastroenteritis. Out of 210 diarrhoea stool samples collected, 27 (13%) tested positive for group A rotavirus. There was a higher prevalence of infection in hospitalised children (63%) as compared to the non-hospitalised ones (37%). Most rotavirus infections occurred in the age 24 months and below. Of the 13 samples which were positive by PAGE, the predominant electrophoretic pattern detected was the short (S) electrophoretype 9/13 (69%) followed by the long (L) electrophoretype 4/13 (31%). The following G types were detected; G2 (17%), G3 (22%), mixed infections found were G1+G2 (5.6%), G1+G8 (22%), G3+G9 (27.8%) and G1+G3+G9 (5.6%). P[6] was the only VP 4 genotype detected. Rotavirus strains G3P[6] and G3+G9P[6] were identified as the circulating strains in north Botswana. The detection of uncommon rotavirus strains and the high proportion of mixed infections suggest a greater diversity of rotavirus infections among children in Botswana than previously reported. Our study reveals a complex epidemiological profile of rotavirus infection in Botswana that may require further molecular characterisation.